2022
DOI: 10.1021/acscatal.2c02445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Addition to Isopropanol for Hydrogenation of Compounds Derived from 5-Hydroxymethyl Furfural over Pd, Ru, and Cu Catalysts

Abstract: We have developed lumped reaction schemes to optimize the yields of products from selective hydrogenations of HAH, a biomass-derived platform chemical produced by two-step aldol condensations of 5-hydroxymethyl furfural (H) with acetone (A). Reaction schemes consisting of 7, 9, and 11 steps were examined to describe the rates of formation of the observed products and reaction intermediates for hydrogenation of HAH over Ru and Pd catalysts, and a 3-step scheme was studied over Cu catalysts. Rate constants and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The product was characterized by 1 H and 13 C NMR and was quantified by GC-FID. 21 2.3 Synthesis of GA-MAL by imidation 3.22 g (33 mmol) of maleic anhydride and 4.81 g (33 mmol) of L-glutamic acid were added into 31.5 g of acetic acid solvent in a 200 mL-scale round-bottom flask. The round flask was placed in an oil bath, set at 170 °C, with reflux and reacted for 120 min under the stirring (600 rpm).…”
Section: Synthesis Of Phah By Aldol-condensation and Hydrogenation 21mentioning
confidence: 99%
See 2 more Smart Citations
“…The product was characterized by 1 H and 13 C NMR and was quantified by GC-FID. 21 2.3 Synthesis of GA-MAL by imidation 3.22 g (33 mmol) of maleic anhydride and 4.81 g (33 mmol) of L-glutamic acid were added into 31.5 g of acetic acid solvent in a 200 mL-scale round-bottom flask. The round flask was placed in an oil bath, set at 170 °C, with reflux and reacted for 120 min under the stirring (600 rpm).…”
Section: Synthesis Of Phah By Aldol-condensation and Hydrogenation 21mentioning
confidence: 99%
“…The unassigned chemical shifts in 13 C NMR spectrum of PHAH-GA-MAL (Fig. S14 †) resulted from PHAH 21 and GA-MAL (Fig. S13 †), formed by retro Diels-Alder reaction during evaporation of THF solvent at 40 °C.…”
Section: Effect Of the Engineered Organocatalysts On Lactose Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic hydrogenation on metal oxide-supported nanoparticles is the highly followed standard industrial protocol for the production of both fine and bulk chemicals. In general, the diffusion of hydrogen atoms across the surface of the metal oxide-supported catalyst is crucial to the hydrogenation because the diffusion can increase the concentration of active H-atoms on the metal oxide surface during the hydrogenation. Therefore, it significantly affects the catalytic performance of metal oxide-supported catalysts. Generally, on the surface of a metal oxide, the diffusion of H-atoms has to overcome a high energy barrier (55–236 kJ mol –1 ), , while on the surface of a noble metal, the energy barrier for dissociation of H 2 or the diffusion of H-atom is almost negligible . Fortunately, water can assist H-atom diffusion across the oxide surface, also known as water-assisted proton hopping (WAPH), via the classic proton coupling electron mechanism. , Specifically, water picks up H-atoms to form a short-lived transition state of hydronium ions (H 3 O + ), accompanied by electron transfer from the H-atom to the d orbital of the metal oxides, which can promote the hydrogenation over metal oxide-supported catalysts. For example, Zhao et al reported that furfural hydrogenation on the Pd/Al 2 O 3 catalyst was accelerated by replacing the cyclohexane solvent with water.…”
Section: Introductionmentioning
confidence: 99%
“…The serious environmental pollution caused by Cu–Cr catalysts requires the development of chromium-free catalysts. In the literature, various transition metal-based catalysts have been reported for hydrogenation of furfural, including Ni, , Co, , Cu, , Ru, Pd, , and Pt, , where a second metal or promoter is sometimes added to increase catalytic activity and/or selectivity.…”
Section: Introductionmentioning
confidence: 99%